Habilidades blandes y empleabilidad en estudiantes de educación inicial de la facultad de ciencias de la educación y humanidades en la Universidad Nacional de la Amazonía Peruana 2021 - Huasanga Pacaya, Paulina (2022)
The purpose of this research study was to determine the relationship between soft skills and employability in initial education students of the Faculty of Education Sciences and Humanities at the National University of the Peruvian Amazon in Iquitos in 2021. The research adopted as a methodology, the relational type with a field, cross-sectional, and bivariate design. The unit of study was the initial education student, the population and sample were 95 fourth and fifth level students. The survey technique and questionnaires were used to obtain the data, which were previously validated through expert judgment. The present study concludes that Kendall's Tau-b correlation coefficient is = 0.213; p = 0.040 which shows a low positive relationship between soft skills and employability in initial education students and that when obtaining a Spearman rho correlation coefficient at = 0.213 *, p = 0.038 it is determined that there is a low direct relationship and significant between soft skills and employability in initial education students of the Faculty of Education Sciences and Humanities at the National University of the Peruvian Amazon, a result that also proves the hypothesis raised.